Economic Valuation of Lake Tempe Area Resources in Wajo Regency; A Socio-Economic and Ecological Approach - Darsam Belana (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
So far, there have been no economic valuation studies to ecological studies that reveal the potential of the Tempe Lake area, so that policy makers have not been able to manage and use the Tempe Lake Area, at the most effective and efficient level, and able to distribute the benefits and costs of conservation fairly. The novelty of this research is trying to do an economic valuation, which is paralleled with an ecological study of the existence of Lake Tempe. This study aims to identify the ecological functions of Lake Tempe that give rise to various economic and non-economic benefits for the community around Lake Tempe, as well as to determine the amount of Total Economic Value (NET) of Lake Tempe. The data were analyzed by adding up the value of direct benefits, value of indirect benefits, value of choice benefits, value of existence benefits and value of inheritance benefits in the Tempe Lake area. This research data was collected through surveys and interviews with stakeholders who have a reciprocal relationship with the Tempe Lake area in Wajo Regency. The results showed that the total economic value obtained for the Tempe Lake area was Rp. 5,742,249,708,120,- per year with the largest contribution coming from the direct benefit value of Rp. 4,571,395,793,250,- per year or 78.7%. The implication of the research is the need for cross-sectoral joint coordination from various levels of government, to encourage the rehabilitation of forest areas around the Walennae and Bila watersheds. Dredging of Lake Tempe is urgently needed to cope with the annual flooding due to overflow of water. In addition, to increase the utilization of Lake Tempe, a more massive synergy between stakeholders is needed, to develop other untapped potential of the Lake Tempe area.Keywords: Valuation; Resource Economics; Ecology